Annual Plan 1999-2000 Proposals Volume III Haryana State - Planning Commission (Planning Commission, 1999)
In the State of Haryana, there are about 13000 Watercourses on the canal system. These Watercourses are earlier unlined and heavy see page losses were occurring. Since the State is short of surface waters, great emphasis was placed on Mining of Watercourses so as to conserve the available irrigation water and utilise the same for providing irrigation facilities to the maximum areas.
Planning Department, Government of Haryana